Nitrous Oxide and Carbon Dioxide Emissions from Aerobic and Anaerobic Incubations: Effect of Core Length. Issue 3 (1st April 2013) - Guo, Xiaobin; Drury, Craig F.; Daniel Reynolds, W.; Yang, Xueming; Fan, Ruqin
Abstract : An important approach for elucidating soil respiration and denitrification processes includes laboratory incubation of uniformly repacked soil cores that are sealed at the base and maintained at constant temperature and water content; however, few studies have considered the impacts of core length on emission of the main respiration and denitrification gases, CO2 and N2 O. Hence, aerobic and anaerobic incubation studies were conducted to evaluate the effect of core length (2.5, 5.0, 7.5, 10.0, and 15.0 cm) on CO2 and N2 O emissions, using sieved (≤4‐mm) and uniformly repacked Brookston clay loam soil maintained at field capacity water content. The shortest core length (2.5 cm) appeared to enhance O2 diffusion unrealistically, and as a result, N2 O emissions under anaerobic conditions and CO2 emissions under aerobic conditions were probably overestimated. A boundary between aerobic and anaerobic respiration apparently occurred at the 8‐ to 10‐cm length due to gravity redistribution of water within the core, and consequently, the 10.0‐ and 15.0‐cm core lengths probably created artifacts by depressing CO2 emissions under aerobic conditions and by stimulating both denitrification and N2 O reduction to N2 under anaerobic conditions. Hence, core lengths of 5.0 to 7.5 cm may provide the most realistic CO2 and N2 O emission results for repacked clay loam soils incubated at near field capacity water content. It was concluded that the most appropriate length for bottom‐sealed incubation cores depends on soil type and water content and that unregulated core length can induce important artifacts into incubation estimates of CO2 and N2 O emissions.